The Role of Sense of Coherence During the COVID-19 Crisis: Does it Exercise a Moderating or a Mediating Effect on University Students’ Wellbeing? - Vanessa Kulcar; Alexander Kreh; Barbara Juen; Heidi Siller (SAGE Open, 2023)
The COVID-19 crisis caused extensive mental health strains. Sense of coherence (SOC) is considered a protective factor for mental health in crisis that might also be decisive during the COVID-19 pandemic, but the mechanisms are not yet well understood. Using longitudinal survey data of 117 Austrian university students collected in 2020, we tested both moderating and mediating effects of SOC for the association of different stressors with later wellbeing. SOC did not buffer but mediated the effects of stressors on wellbeing. Students especially suffered from reduced feelings of manageability when confronted with financial strains, dissatisfying study situations, or disrupted plans. Supporting them in managing the difficulties of the crisis should therefore be considered a crucial part of psychosocial support.